Isolation of chemically well-defined semipreparative liquid chromatography fractions from complex mixtures of proanthocyanidin oligomers and polymers - Milla M. Leppä; Maarit Karonen; Petri Tähtinen; Marica T. Engström; Juha-Pekka Salminen (Elsevier B.V., 2022)
In this study, a semipreparative liquid chromatography method was developed for the isolation of chemically well-defined proanthocyanidin (PA) oligomer and polymer fractions. The aim was to achieve better separation than traditionally achieved for the PAs with other chromatographic methods. The method was tested with eleven PA rich Sephadex LH-20 fractions, which originated from eleven different plant species. The resulting semipreparative fractions were analyzed by both triple quadrupole and high-resolution mass spectrometry assisted by ultrahigh-performance liquid chromatography (UPLC) separation. The results showed remarkable differences in the procyanidin to prodelphinidin ratio, mean degree of polymerization, and specific oligomeric and polymeric content. However, some of these features indicated consistent patterns between species as the function of UPLC retention time. The developed method enables the production of tens of well-defined fractions of PA oligomers and polymers from the unresolved chromatographic PA hump. Accordingly, this allows researchers to explore the most bioactive parts of the complex PA humps of any plant species, which have not been possible earlier.